Optimizing Maintenance Efficiency with OEE Method: Mengoptimalkan Efisiensi Pemeliharaan dengan Metode OEE - Putera, Alfien Ramadhan Syach; Marodiyah, Inggit (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the effectiveness of roving machines in a production environment by employing the Overall Equipment Effectiveness (OEE) methodology. High downtime of the roving machine significantly hampers production processes, leading to reduced machine performance and speed, resulting in suboptimal OEE values. Through OEE calculations, a value of 66.92% was obtained, highlighting considerable room for improvement towards achieving world-class standards. The findings underscore the necessity for targeted enhancements to mitigate machine downtime, thereby enhancing overall production efficiency and competitiveness in the manufacturing sector. Highlights : Efficient utilization of roving machines through OEE optimization is crucial for enhancing production performance. High downtime of roving machines significantly impedes production processes, leading to decreased efficiency and competitiveness. Addressing downtime issues can lead to substantial improvements in overall production efficiency, aligning operations with global standards. Keywords: Roving machine, Overall Equipment Effectiveness (OEE), Production efficiency, Downtime reduction, Manufacturing competitiveness